(untitled) (Memorias Sifored - Encuentros Educación UAN, 2021)
Abundant scientific literature has addressed the problem of comprehensive reading and its direct relation to the solution of mathematical problems. In that sense, making visible the relationship between the two areas, a didactic strategy was designed, and it responds to the process of compression and analysis of texts for the solution of problems developing and making use and of logical connectors, interpretation, construction and inference of images or graphics. The sample consisted of ten students from third grade. To address this difficulty, a qualitative and quasi-experimental design work was proposed. A didactic strategy was developed with three main instruments. The goal of the first one was to characterize the population, and it consisted of nine questions. The second one, a diagnostic test, consisted of five questions, which had a directed structure into an interpretative/inferential reading, and solution of mathematical problems. And finally, three working guides with a story type were presented to the sample. The instruments were analyzed by two rubrics. The results show a remarkable improvement in the solution of mathematical problems, derived from a better reading comprehension. Through of a conscious, critical and objective reading it was possible to obtain adequate information to infer, organize and structure information which was useful for give a solution to a problem situation. The skills in text comprehension help significantly to the communicative skills that contribute to problem solving strategies.